2014
DOI: 10.7251/els1418029s
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Capacitor Parameters Using Vector Network Analyzers

Abstract: Abstract-Vector network analyzer (VNA) is versatile measuring equipment which is primarily used for two-port device S parameters measurements. This paper addresses measurement of capacitor parameters using VNA in broad frequency range. The main attention is focused on the measurement accuracy of capacitors parameters using VNA and proper de-embedding of an experimental setup parasitics to get accurate results. Comparative measurement error analysis for different measurement techniques is presented. Suitability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…The measured initial gap is found to be more than the thickness of deposited sacrificial layer (t SiO 2~3 00 nm) due to bowing of the bridge under film-stress. The change in capacitance between the suspended bridge and the gate electrode as a function of actuation (emitter-gate) potential (V a ) is measured using a vector network analyzer [39][40][41] . The details of measurement setup are provided in the Supplementary Note 7.…”
Section: Resultsmentioning
confidence: 99%
“…The measured initial gap is found to be more than the thickness of deposited sacrificial layer (t SiO 2~3 00 nm) due to bowing of the bridge under film-stress. The change in capacitance between the suspended bridge and the gate electrode as a function of actuation (emitter-gate) potential (V a ) is measured using a vector network analyzer [39][40][41] . The details of measurement setup are provided in the Supplementary Note 7.…”
Section: Resultsmentioning
confidence: 99%
“…Capacitance measurements were obtained before and after the incubation of Cryptosporidium using a network analyzer (N5241A, Agilent Technologies, Santa Clara, CA, USA) connected to a coplanar waveguide probe which makes a calibrated impedance measurement referenced to the contact interface of the electrodes. S-parameter measurements [30] were performed ver a frequency range of 5.5 GHz to 8.5 GHz and converted to equivalent circuit capacitance values. The network analyzer was calibrated using the SOLT (short-open-load-through) method, and the S-parameter values were recorded at two different stages: (1) after SAM formation with immobilized anti- Cryptosporidium antibodies, and (2) after incubating the sensor with various concentrations of Cryptosporidium .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…However, the measurement error increases rapidly when the impedance differs from 50 Ohms. In order to perform accurate extraction of a low inductance over a wide frequency range, 2-port S-parameters techniques, such as Shunt-Thru and Series-Thru (in Figure 6b,c, respectively), are preferred to the 1-port measurement [28,29]. It has been shown that when the impedance value is below 50 Ω, the Shunt-Thru measurement demonstrates the best accuracy.…”
Section: S-parameter Measurement Techniquesmentioning
confidence: 99%